Optimization Production of Synthetic Recombiant Analgesic Peptide Molecules in Yeast by using Taguchi Methodology. - Rao, J. Vekateshwara (International Journal of Psychosocial Rehabilitation, 2020)
The analgesic peptide synthetic genes with signal peptides were sub cloned into the pCTON2 for expression in yeast. The recombinant plasmids were used to transform under the gal promoter of yeast. The L-8 orthogonal array was selected for screening of the factors and interaction between seven factors selected: size of inoculum, temperature, orbital speed, time of induction, concentration of antibiotics, volume of container and media at two levels. After screening, more effective factors and their interactions were optimized using L8 and experimental configuration of orthogonal arrays. Qualitek-4 software was used for automatic design and standard ANOVA method of Taguchi experiments. ANOVA has revealed and identified the effect of each factor and the optimum conditions and estimated the performance of the each condition was evaluated. Currently, the achievable volumetric productivities for yeast cultivations are reaching about 1-2 mg/L/h, which exceed that of most of the mammalian cell productivities (~0.5–1.0 mg/L/h). The expected Taguchi results indicated soluble analgesic peptides expression level of 48 mg/l under optimal conditions can be achievable in shake flask cultures by using Taguchi Method. The same value o of 45 mg was obtained experimentally for analgesic opioid peptide expression under optimum conditions in shake flasks. pH, RPM and size of the inoculums have been identified as crucial factors as per the optimization and statistically suggested methods and rest of the factors are kept at normal conditions.